2010
DOI: 10.1371/journal.pbio.1000558
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin Contributions to Irradiance Coding in the Thalamo-Cortical Visual System

Abstract: Neurophysiological and anatomical studies identify melanopsin expressing retinal ganglion cells (mRGCs) as a major source of information in the mouse visual system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
276
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(308 citation statements)
references
References 71 publications
(86 reference statements)
21
276
1
1
Order By: Relevance
“…Within the retina, the melanopsin-expressing ipRGCs are thought to provide the primary irradiance signal (Wong, 2012). The ipRGC irradiance code is already known to impact conventional vision by setting pupil size (Lucas et al, 2003), adapting visual circuits (Allen et al, 2014;Hankins and Lucas, 2002;Zhang et al, 2008), and regulating maintained firing (Brown et al, 2010). Our demonstration that irradiance control of oscillations can be modulated by changes in spectral power density targeting melanopsin and is impaired in melanopsin knockouts argues that melanopsin (and thus ipRGCs) also plays a central role in this aspect of vision.…”
Section: Discussionmentioning
confidence: 99%
“…Within the retina, the melanopsin-expressing ipRGCs are thought to provide the primary irradiance signal (Wong, 2012). The ipRGC irradiance code is already known to impact conventional vision by setting pupil size (Lucas et al, 2003), adapting visual circuits (Allen et al, 2014;Hankins and Lucas, 2002;Zhang et al, 2008), and regulating maintained firing (Brown et al, 2010). Our demonstration that irradiance control of oscillations can be modulated by changes in spectral power density targeting melanopsin and is impaired in melanopsin knockouts argues that melanopsin (and thus ipRGCs) also plays a central role in this aspect of vision.…”
Section: Discussionmentioning
confidence: 99%
“…ipGRCs have been shown to use a rhabdomeric-like phosphoinositide cascade involving the effector enzyme PLC (18,41). Very recently, it has been observed that these melanopsin-expressing ganglion cells extend their projections toward the thalamo-cortical neurons implicated in pattern vision, establishing melanopsin-based photoreception as a significant source of visual information to the thalamo-cortical pathway, independent of rods or cones (43). The ipGRCs and the fly phototransduction mechanisms also share other similarities: both require a member of the Gq/11 family of G proteins as a mediator of the phototransduction cascade, and, in both cases, the phototransduction cascade is tightly coupled to the plasma membrane and involves light-sensitive channels belonging to the TRP family (44).…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, some data concerning the potential roles performed by M4-type pRGCs. The nature and properties of light responses recorded from cells within the dLGN have suggested a role for melanopsin in encoding changes in background [18][19][20] and the modulation of visual responses, with melanopsin reportedly driving adaptation of visual responses, modulating visual feature selectivity and facilitating a more reliable encoding of complex visual signals. 22,23 Based on retrograde labelling studies, it would seem that M4-type pRGCs project almost exclusively to the dLGN, 39 and would, therefore, seem to be predominantly tasked with providing input to visual pathways.…”
Section: Physiological Roles Performed By Prgc Subtypesmentioning
confidence: 99%
“…17 More recently it has become clear that melanopsin contributes not only to a range of NIF pathways but also performs multiple roles in image forming visual pathways. Melanopsin provides visual centres with information regarding overall levels of environmental light, and performs roles in irradiance coding and brightness discrimination, [18][19][20] contrast detection, 21 and adaptation of visual responses. 22 Melanopsin also acts as an irradiance detector for the retina, 22,23 providing measures of overall illuminance and facilitating the adaptation of cone photoresponses under bright-light conditions.…”
mentioning
confidence: 99%